Flow experience in foreign language writing: Its effect on students’ writing process and writing performance - Liu, Ping; Zhang, Yao; Liu, Dilin (Frontiers in Psychology, 2022)
This research investigates Chinese EFL students’ flow experience in academic writing and its effect on students’ writing performance. The research consists of two studies: (1) a preliminary study involving a survey of 162 college students immediately after their completion of a short English essay to examine whether and how intensely they experienced flow during their writing and whether their perceived levels of challenge of the writing task and their writing skills affected their flow experience, and (2) a main study including a survey of 216 different students at the end of a semester-long writing course to ascertain how frequently these students experienced flow during the course, whether their intrinsic writing motivation and attention control ability were significantly correlated with their flow experience, and whether their flow frequency had an effect on their performance in the writing course. Results of statistical tests (including Class Factor Analyses and regression analyses) of the data in the preliminary study revealed that a large majority (76%) of the students experienced a certain level of flow in their writing and their perceived levels of writing skills had a significant influence on their flow experience. The statistical test results of the main study indicated that (1) 66.4% of the students experienced flow with various frequency levels while 33.6 % of the students rarely or never experienced flow, (2) students’ level of motivation and attention control were significantly correlated with their level of flow frequency, and (3) students’ flow frequency had a significant influence on their writing course scores. Research and pedagogical implications of the study are also discussed.